National trends in incidence and geographic distribution of melanoma and keratinocyte carcinoma in the Russian Federation - Muntyanu, Anastasiya; Ghazawi, Feras M.; Pastukhova, Elena; Zubarev, Andrei; Litvinov, Ivan V. (Frontiers in Medicine, 2023)
Keratinocyte Carcinomas (KC), including basal cell and cutaneous squamous cell carcinomas, are the most common skin cancers in Fitzpatrick phototype I-III individuals, while melanoma is one of the deadliest skin cancer types. The incidence of both melanoma and KC is increasing in Russia. KCs’ incidence increases from north-to-south across the Russian Federation. In contrast, while melanoma’s incidence increases from north-to-south in the eastern part of the country, in the west of Russia a reverse latitude gradient trend is noted, where northern more affluent regions of Russia display higher rates of melanoma than the southern jurisdictions. Furthermore, our detailed analysis of incidence by jurisdiction highlights that affluent northern capital cities have higher rates of melanoma than the surrounding regions. The observed melanoma incidence trends in the western portion of Russia are similar to the findings in the western Europe and opposite of the findings in Canada.